Flavokawain B inhibits the growth of acute lymphoblastic leukemia cells via p53 and caspase-dependent mechanisms. Issue 8 (3rd August 2015) - Tang, Yan-Lai; Huang, Li-Bin; Tian, Yun; Wang, Li-Na; Zhang, Xiao-Li; Ke, Zhi-Yong; Deng, Wu-Guo; Luo, Xue-Qun
Abstract : The development of novel chemotherapeutic drugs is needed for the treatment of patients with acute lymphoblastic leukemia (ALL). In this study, the anti-leukemic effect and the potential molecular mechanisms of action of flavokawain B on ALL were investigated. Flavokawain B was found to significantly inhibit the cellular proliferation of B-ALL and T-ALL cell lines in a dose-dependent manner. It also induced cellular apoptosis by increasing the expression of p53, Bax and Puma, and activating the cleavage of caspase-3 and poly ADP-ribose polymerase (PARP). Furthermore, the enhancement of p53-dependent apoptosis by flavokawain B could be rescued by pifithrin-α, a pharmacological inhibitor of p53 transcriptional activity. Moreover, the proliferation of leukemia blast cells from 16 patients with ALL was inhibited by flavokawain B, and tumor growth in xenograft mice was also suppressed by this drug. In conclusion, our results demonstrate the therapeutic potential of flavokawain B for the treatment of ALL.